Sustainable Agricultural Value Chain - Alem, Habtamu; Ranjan Jena, Pradyot (IntechOpen, 2022)
The book discusses scientific, technical, and sociological aspects of sustainable agricultural value chains, focusing on coffee and tea production. The book advocates a value-chain strategy and highlights the importance of tracking the effects of climate change. Increasing the amount of value-added products via irrigation is critical to combating climate change and achieving sustainable development. Furthermore, blockchain technology has the potential to transform agricultural business models and supply chain networks.